Acoustic Noise Mitigation of Switched Reluctance Machines With Leaf Springs - Yasa, Yusuf; Sozer, Yilmaz; Garip, Muhammet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
In this article, a leaf spring insertion to the stator back iron is proposed to reduce vibration and acoustic noise in a switched reluctance machine (SRM). The back iron of the tooth tip is curved out and the material made up of carbon spring steel is placed to dampen the vibration due to radial force. A 6/4 stator/rotor pole SRM is designed and its natural vibration mode frequencies are determined through finite-element analyses. The optimal current waveform is applied to the SRM model using the multidisciplinary coupled simulation method to determine the radial force with the harmonic orders. In the final step, the proposed leaf spring architecture is optimized to achieve the most dampening for the effective radial force harmonic orders. The simulation and experimental results confirmed the effectiveness of the leaf spring insertion in reducing the noise and vibration in SRMs.
Keywords: Springs; Stators; Vibrations; Reluctance motors; Acoustic noise; Force; Stator windings; leaf spring; switched reluctance machine (SRM); vibration; REDUCTION; CANCELLATION; Automation & Control Systems; Engineering; Instruments & Instrumentation